Do sporting activities convey benefits to bone mass throughout the skeleton? - Nevill, A.; Holder, R.; Stewart, A. (Journal of Sports Sciences, 2004)
It is well known that sport and exercise play an important role in stimulating site-specific bone mineral density (BMD). However, what is less well understood is how these benefits dissipate throughout the body. Hence, the aim of the present study was to compare the BMD (recorded at nine sites throughout the skeleton) of 106 male athletes (from nine sports) with that of 15 male non-exercising age-matched controls. Given that BMD is known to increase with body mass and peak with age, multivariate and univariate analyses of covariance were performed to compare the BMD of the nine sports groups with controls (at all sites) using body mass and age as covariates. Our results confirmed a greater adjusted BMD in the arms of the upper-body athletes, the right arm of racket players and the legs of runners (compared with controls), supporting the site-specific nature (i.e. specific to the externally loaded site) of the bone remodelling response (all P <0.01). However, evidence that bone mass acquisition is not just site-specific comes from the results of the rugby players, strength athletes, triathletes and racket players. The rugby players' adjusted BMD was the greatest of all sports groups and greater than controls at all nine sites (all P <0.01), with differences ranging from 8% greater in the left arm to 21% in the lumbar spine. Similarly, the strength athletes' adjusted BMD was superior to that of controls at all sites (P <0.05) except the legs. The adjusted BMD of the triathletes was significantly greater than that of the controls in both the arms and the legs as well as the thoracic and lumbar spine. The racket players not only had significantly greater right arm BMD compared with the controls but also a greater BMD of the lumbar spine, the pelvis and legs. In contrast, the low-strain, low-impact activities of keep-fit, cycling and rowing failed to benefit BMD compared with the age-matched controls. These results suggest that sporting activities involving high impact, physical contact and/or rotational forces or strains are likely to convey significant benefits not only to the loaded sites, but also to other unloaded peripheral and axial sites throughout the skeleton.